Vegetation development in old fields at the UWM Field Station - (:unkn) unknown (My University, 1991)
We studied abandoned fields at the UW-Milwaukee Field Station in 1990 to determine how previous cropping history and management practices have influenced present vegetation composition. Eleven fields were sampled for herbaceous species presence and coverage, and species compositions were analyzed by Detrended Correspondence Analysis ordination. Nearly all the fields were abandoned in the mid-1960's. Standing crop biomass of the herbaceous vegetation peaked in late July. Fields with very recent management (last 5 years) in the form of mowing or burning differed in species composition from fields without recent management and fields that have been unmanaged since abandonment. Species such as Poa spp., Bromus inermis, and Solidago altissima were common to nearly all the fields. However, recently managed fields were distinguished by the presence of a group of weedy, exotic species in contrast to the presence of many perennial native species in fields without recent management. Crop history, soil type, and field proximity did not have strong influences on species composition.
Keywords: old fields; abandoned fields; UWM Field Station; vegetation development